PRAGMATIST: A tool to prioritize foot-and-mouth disease virus antigens held in vaccine banks - Ludi, Anna B.; McLaws, Melissa; Armson, Bryony; Clark, Jessica; Di Nardo, Antonello; Parekh, Krupali; Henstock, Mark; Muellner, Petra; Muellner, Ulrich J.; Rosso, Fabrizio; Prada, Joaquin M.; Horton, Daniel L.; et al. (Frontiers in Veterinary Science, 2022)
Antigen banks have been established to supply foot-and-mouth disease virus (FMDV) vaccines at short notice to respond to incursions or upsurges in cases of FMDV infection. Multiple vaccine strains are needed to protect against specific FMDV lineages that circulate within six viral serotypes that are unevenly distributed across the world. The optimal selection of distinct antigens held in a bank must carefully balance the desire to cover these risks with the costs of purchasing and maintaining vaccine antigens. PRAGMATIST is a semi-quantitative FMD vaccine strain selection tool combining three strands of evidence: 1) estimates of the risk of incursion from specific areas (source area score); 2) estimates of the relative prevalence of FMD viral lineages in each specific area (lineage distribution score); and 3) effectiveness of each vaccine against specific FMDV lineages based on laboratory vaccine matching tests (vaccine coverage score). The output is a vaccine score, which identifies vaccine strains that best address the threats, and consequently which are the highest priority for inclusion in vaccine antigen banks. In this paper, data used to populate PRAGMATIST are described, including the results from expert elicitations regarding FMD risk and viral lineage circulation, while vaccine coverage data is provided from vaccine matching tests performed at the WRLFMD between 2011 and 2021 (n=2150). These data were tailored to working examples for three hypothetical vaccine antigen bank perspectives (Europe, North America, and Australia). The results highlight the variation in the vaccine antigens required for storage in these different regions, dependent on risk. While the tool outputs are largely robust to uncertainty in the input parameters, variation in vaccine coverage score had the most noticeable impact on the estimated risk covered by each vaccine, particularly for vaccines that provide substantial risk coverage across several lineages.